1985
DOI: 10.1002/pssb.2221280204
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of the Quaternary II–VI Mixed Crystals in the Far Infrared Region

Abstract: The optical properties of mixed crystals CdTel -x-n/SexSn/ andZnTe1 -,-ySe,Sy are investigated by methods of far infrared spectroscopy. Different types of transformation of the vibrational spectra of these solid solutions with composition are found. The longitudinal and transverse optical vibration frequencies are calculated theoretically by means of a unit cellversion of the random element isodisplacement model. The calculations are in satisfactory agreement with the experimental results. The reflection spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…-TO Te Zn−Se band. The LO-TO inverted splitting is large at intermediate x values, and further increases with (1−x), as evidenced by Burlakov et al 13 Then it vanishes in the Te-and Sedilute limits, as observed by Yang et al 19 In brief, all the 'anomalous' features in the Raman/IR spectra of ZnTeSe find a natural assignment within the percolation model, on a quantitative basis. Actually, in retrospect there is a quasi-perfect analogy between the phonon mode behaviors of ZnTeSe (this work) and InGaP (Ref.…”
Section: (To Lo) Raman Lineshapesmentioning
confidence: 72%
See 3 more Smart Citations
“…-TO Te Zn−Se band. The LO-TO inverted splitting is large at intermediate x values, and further increases with (1−x), as evidenced by Burlakov et al 13 Then it vanishes in the Te-and Sedilute limits, as observed by Yang et al 19 In brief, all the 'anomalous' features in the Raman/IR spectra of ZnTeSe find a natural assignment within the percolation model, on a quantitative basis. Actually, in retrospect there is a quasi-perfect analogy between the phonon mode behaviors of ZnTeSe (this work) and InGaP (Ref.…”
Section: (To Lo) Raman Lineshapesmentioning
confidence: 72%
“…Representative sets of (TO, LO) frequencies in ZnTeSe obtained from Raman/IR analysis, as taken in the literature, 13,19,20 are displayed in Fig. 3.…”
Section: Percolation Picture For Znte1−xsexmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the IR spectra of ZnSeTe -type (ii) -exhibit two clear resonances [4], while only one was expected from the MREI approach. Also, reWe discuss the classification of the phonon type behavior of semiconductor alloys as apparent in the Raman and infrared spectra, i.e.…”
mentioning
confidence: 91%